Introduction of Digital Literacy Skills by Parents in Early Childhood to Prevent Mobile Phone Addiction Behavior - Lestari, Dwi Puji; Ramadhanti, Safira; Asih, Siti Nur; Putri, Dwi Andesta; Nopiana, Nopiana (Journal of Early Childhood Education (JECE), 2024)
Data from the Central Statistics Agency (BPS) in 2022 indicate that 34.44% of early childhood children in Indonesia have used gadgets. However, the implementation of digital literacy by parents has not kept pace. A survey conducted in Semarang revealed that 73.9% of parents had not introduced digital literacy to their children. This study aims to provide an overview of how parents introduce digital literacy skills to early childhood children as a preventive measure against gadget addiction. The research employed a descriptive quantitative method using a survey approach. The data source consisted of 94 parents in Jakarta. A purposive sampling technique was used, considering the parents’ educational background and their status as caregivers of children aged 0–8 years. The questionnaire was distributed through Google Forms. The instrument comprised 16 closed-ended questions regarding the introduction of digital literacy skills and behaviors related to gadget addiction as reported by the respondents.Data were analyzed using simple descriptive statistical analysis by presenting figures and diagrams, as well as qualitative analysis through the interpretation of research data. The findings indicate that the majority of parents in Jakarta have introduced digital literacy to their children.